2015
DOI: 10.1177/0888406415599430
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Enhanced Knowledge and Use of Secondary Transition Evidence-Based Practices

Abstract: Students with disabilities lag behind peers without disabilities in most postsecondary outcome areas such as employment, postsecondary education, and independent living. Numerous initiatives aimed at supporting students as they transition from school to adult life have received attention over the last few decades. These initiatives include those that focus on preparing secondary special educators and transition personnel to be better equipped to facilitate these transitions. In this study, the authors examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…They also found 45.3% of participants were seldom or never given secondary transition EBP resources. Plotner, et al (2016) also found that the majority of transition professionals receive limited transition EBP training. Almost half of special educators and almost one-third of direct-service transition professionals received one day or less of transition EBP training per year.…”
Section: Lack Of Preparation According Tomentioning
confidence: 88%
See 4 more Smart Citations
“…They also found 45.3% of participants were seldom or never given secondary transition EBP resources. Plotner, et al (2016) also found that the majority of transition professionals receive limited transition EBP training. Almost half of special educators and almost one-third of direct-service transition professionals received one day or less of transition EBP training per year.…”
Section: Lack Of Preparation According Tomentioning
confidence: 88%
“…Research on general secondary educators' perceptions related to their involvement in the transition process is needed. While limited research has been conducted on special education teachers' and transition personnel's perspectives on roles and responsibilities related to implementing transition services (Blanchett, 2001;Benitez, et al, 2009;Plotner, et al, 2016), I found no research focused solely on perceptions of general education teachers' roles. Lazaroff (2013) did include general educators among a variety of professionals in his study.…”
Section: Statement Of Problem and Research Questionmentioning
confidence: 93%
See 3 more Smart Citations